Analysis on brand preference and loyalty of physical education and sports teachers - Orhan, Serdar; Kaplan, Zeynep (Horizon Research Publishing, 2018)
The purpose of this study is to determine the factors affecting brand preference and loyalty of physical education and sports teachers and to analyse it according to the demographic characteristics. The research population is composed of 265 physical education teachers working in Elazığ province. The research sample is composed of 158 male and 39 female as a total of 197 voluntary physical education teachers working in Elazığ province in 2016-2017 academic year. As a data collection tool, Personal Information Form prepared by the researcher and Brand Preference and Loyalty Scale developed by Çifci were used. Mann Whitney U and Kruskal Wallis H tests among the statistical analyses were used and p<0.05 was accepted as the significance level. In conclusion, high preference of physical education teachers with an income level of 2001-2500 TL for branded product and the low level loyalty of physical education teachers with a bachelor degree for branded products were significant. It has been observed that the physical education teachers working as permanent teachers in public schools consider brand and quality equal and they attach importance to the quality in preferring branded products. It has been determined that the higher the demand for branded products is, the higher the income level becomes. The brands of Adidas, Nike and Hummel have been found to be preferred more. © 2018 by authors, all rights reserved.
Keywords: Attitude; Brand; Buying; Preference; Sports